2021
DOI: 10.1007/s11606-021-07095-8
|View full text |Cite
|
Sign up to set email alerts
|

Do Urine Drug Tests Reveal Substance Misuse Among Patients Prescribed Opioids for Chronic Pain?

Abstract: BACKGROUND: Urine drug testing (UDT) is a recommended risk mitigation strategy for patients prescribed opioids for chronic pain, but evidence that UDT supports identification of substance misuse is limited. OBJECTIVE: Identify the prevalence of UDT results that may identify substance misuse, including diversion, among patients prescribed opioids for chronic pain. DESIGN: Retrospective cohort study. SUBJECTS: Patients (n=638) receiving opioids for chronic pain who had one or more UDTs, examining up to eight sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[4][5][6][7] The sensitivity and specificity of the ICD codes for opioid abuse and dependence OUD will allow adjustment of findings from previous studies making them more internally valid. 17,22 Future algorithm refinements include machine learning approaches for text mining, inclusion of urine testing results, 23 and comparison with ICD-10 OUD codes alone.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] The sensitivity and specificity of the ICD codes for opioid abuse and dependence OUD will allow adjustment of findings from previous studies making them more internally valid. 17,22 Future algorithm refinements include machine learning approaches for text mining, inclusion of urine testing results, 23 and comparison with ICD-10 OUD codes alone.…”
Section: Discussionmentioning
confidence: 99%
“…Such equivocal UDS findings appear to occur frequently as research has shown that, within a 12-month period in which OMPs underwent regular drug testing, up to 24% of patients exhibit at least one result indicating non-detection of prescribed drug. 14 These findings highlight the need for additional adherence monitoring strategies that provide more accurate and definitive data.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Cheatle et al demonstrated that primary care patients with chronic pain, who were carefully screened via several measures to identify comorbid psychiatric diagnoses, functional impairment, and substance use disorders (SUDs), had low rates of problematic substance use and almost no aberrant behaviors when treated with opioid medications. 17 Additionally, a chart review of urine drug test (UDT) results performed primarily by immunoassay testing (with its known limitations 18 ), suggested that 37 percent of patients with pain prescribed opioids had test results indicating illicit substance use and/or medication misuse. While this study was published recently, the UDT results were obtained between 2014 and 2016 and may not characterize today's opioid-treated patients with pain.…”
Section: Introductionmentioning
confidence: 99%